Argentina and the Pope from the End of the World: Antecedents and Consequences - Fabris, Mariano (2013)
The appointment of Cardinal Bergoglio as the new pontiff of the Catholic Church has had a media impact that exceeded all expectations. The international press, in fact, had taken no notice of him before the conclave; even the best of the Vaticanologists erred in their calculations. Even so, all it took was a few gestures from Pope Francis to conquer the attention of the Catholic world, which was shaken and seduced by his transparent, warm gestures. Camera flashes and questions from analysts beset him. Who was Jorge Mario Bergoglio? An endless number of biographical facts about the Argentine pope began to circulate that, taken separately, amounted to no more than a handful of scattered crumbs. Reading between the lines, however, reveals a man who had a meteoric ecclesiastical career, with repeated sojourns abroad that surely facilitated his designation as cardinal (‘Prince of the Church’) in 2002.